The Representation of Educational Values in Memes: A Semiotic Analysis of Meme Content on Facebook: Representasi Nilai Edukasi Dalam Meme: Analisis Semiotika Konten Meme di Facebook - Al-Azizy, Muhammad Naufal; Prihatin, Titi (Academia Open, 2026)
General Background Digital culture has established new spaces for visual communication, transforming online imagery into significant discursive units for societal interaction. Specific Background On specific networking platforms, these visual texts convey layered meanings that extend beyond mere entertainment to encompass potential instructional content. Knowledge Gap Previous literature predominantly explores these visuals as political critique or popular culture, leaving their pedagogical dimensions and informal knowledge construction largely unexamined. Aims This descriptive qualitative study analyzes the depiction of instructional tenets within these digital posts utilizing Roland Barthes’s sign systems and Stuart Hall’s constructivist framework. Results Findings reveal that creators successfully embed interdisciplinary knowledge—spanning botany, biology, pure science, and socio-religious topics—using intentional visual and linguistic strategies termed educational smuggling. Comedy functions as a transitional medium to translate complex scholarly concepts into communicative formats, fostering participatory knowledge construction between creators and audiences within digital spaces. Novelty This research integrates Barthes's and Hall’s theories to specifically decode informal pedagogical content, establishing a comprehensive analytical structure for digital instructional media. Implications Educators are encouraged to adopt smuggling strategies by inserting academic material into trending visual templates, thereby lowering cognitive resistance and facilitating material contextualization through everyday digital culture. Highlights Intentional visual comedy successfully translates complex scholarly concepts into accessible formats for digital audiences. The strategy of educational smuggling allows creators to embed interdisciplinary knowledge seamlessly into trending online templates. Virtual interactions transform passive content consumption into participatory environments for collective learning alongside misinterpretation clarification. Keywords Educational Smuggling; Roland Barthes Semiotics; Stuart Hall Representation; Digital Visual Culture; Interdisciplinary Knowledge